Non-invasive Serological Monitoring for Crohn's Disease Postoperative Recurrence. (11th June 2022) - Hamilton, Amy L; De Cruz, Peter; Wright, Emily K; Dervieux, Thierry; Jain, Anjali; Kamm, Michael A
Abstract: Introduction: Crohn's disease recurs after intestinal resection. This study evaluated accuracy of a new blood test, the Endoscopic Healing Index [EHI], in monitoring for disease recurrence. Methods: Patients enrolled in the prospective POCER study [NCT00989560] underwent a postoperative colonoscopic assessment at 6 [2/3 of patients] and 18 months [all patients] following bowel resection, using the Rutgeerts score [recurrence ≥i2]. Serum was assessed at multiple time points for markers of endoscopic healing using the EHI, and paired with the Rutgeerts endoscopic score as the reference standard. Results: A total of 131 patients provided 437 serum samples, which were paired with endoscopic assessments available in 94 patients [30 with recurrence] at 6 months and 107 patients [44 with recurrence] at 18 months. The median EHI at 6 months was significantly lower in patients in remission [Rutgeerts <i2] than those with recurrence; p = 0.033. The area under the receiver operating curve [AUROC] for EHI to detect recurrence at 6 months was comparable to that of faecal calprotectin [0.712 vs 0.779, p = 0.414]. EHI of <20 at 6 months had a negative predictive value of 75.7% (95% confidence interval [CI] 58.8–88.2), and sensitivity of 70% [95% CI 50.6–85.3] for detecting recurrence. Combining all time points, an EHI <20 had a negative predictive value of 70.3%. Changes in EHI significantly associated with changes in Rutgeerts scores over the 18 months. Conclusions: The non-invasive multi-marker EHI has sufficient accuracy to be used to monitor for postoperative Crohn's disease recurrence. A monitoring strategy that combines EHI with ileocolonoscopy, with or without faecal calprotectin, should now be prospectively tested.